Entscheidungsprozesse am inklusiven Übergang Eine Grounded Theory Studie im Längsschnitt - Felbermayr, Katharina (Inklusion, Behinderung, Gesellschaft. Bildungs-und sozialwissenschaftliche Beiträge, 2023)
Based on a qualitative, longitudinal and constructivist research approach, the project at hand explores the decision-making process within the inclusive transition from secondary school I to further education from the perspectives of teenagers with disabilities and parents (with/without disabilities). The narratives of 5 families (3 teenagers with disabilities, 3 fathers, 5 mothers with/without disabilities) are of interest. The interviews were conducted three times (every year) during the transition-/decision-making process along the method of intensive interviewing (Charmaz 2014). The analysis of the qualitative data (32 interviews) was based on the coding process according to Charmaz (2014). Through data analysis three types of decision-making could be identified (giving up decision, forcing decision, taking over decision) as subforms of two higher-level decision-making mechanisms named make an independent decision and make a(n) (independent) decision with support. The expectation of an independent decision-making individual is central for teenagers with disabilities and their parents. Different types of "volition" are connected to the decision-making processes, depending on if the teenagers with disabilities make an independent decision (really want it), make a decision with support ((don't) want it) or make a decision owing to given opinions (have to). Due to the longitudinal research design the educational trajectories of teenagers with disabilities are also reconstructed.